EVALUATION OF LITHUANIAN CONSUMERS’ ATTITUDES TO GENETICALLY MODIFIED FOOD - Ingrida Lukošiut&#; Laura Petrauskait&#-Senkevič (Journal of Agribusiness and Rural Development, 2017)
The aim of this investigation is to present the results obtained during the survey of Lithuanian consumers in order to identify their attitudes towards food with genetically modified organisms (GMO). Investigating the consumers approach to genetically modified (GM) food, the following were considered: consumers’ opinions on GMO were analyzed, their knowledge about the presence of food containing GMO on the Lithuanian market, the mandatory GM food labelling, the behavior to a transgenic product while shopping, as well as consumers’ willingness to purchase such products. Data were gathered through a survey of 1000 Lithuanian residents. The empirical results indicated that the majority of the respondents’ attitudes towards food containing GMO are negative. The older consumers with less income are more against GM food compared to younger, wealthier households. 72% of consumers know that if the food contains GMO it must be indicated on the label. However, many consumers who oppose GMO do not try to avoid paying attention to the components of the product listed on its label. Only about a quarter of consumers while buying a product look for such information. This indicates that consumers are not really interested in whether or not the product contains GMO